Analisis Kontribusi Pendapatan dan Kelayakan Hidup Karyawan UMKM Getuk Goreng Sokaraja - Ramanda, Gian; Gunawan, Ratna Setyawati; Fauzi, Pahrul (Lingka Ekonomika, 2022)
This study aims to analyze the income contribution of the Getuk Goreng Sokaraja MSME employees and to analyze the living feasibility of the Getuk Goreng Sokaraja MSME employees. The data used in this study were primary and secondary and used cross tabulation analysis techniques. The results showed that the income contribution of Getuk Goreng Sokaraja MSME employees to the income of large families. It is shown that 63.3 percent of respondents have a contribution of 50 percent to family income. The survival rate of the Getuk Goreng Sokaraja MSME employees is categorized as still below the KHL level in Banyumas Regency. It is shown that 96.67 percent have income below the KHL. Some things that can be considered in increasing the contribution of income to household needs are the need to have a side job in order to get additional income from other sources, as well as the need to improve the wage system, namely calculating the number of hours worked for a month multiplied by the hourly wage. This is certainly very effective if implemented because employees will get monthly income in accordance with the hours worked. In overcoming the inadequacy of life, it is necessary to increase household income by obtaining it through family members who are of productive age or fit to work to work or have a business, in order to earn income as an additional contribution to household income.